ASEAN Dan Penguatan Rule of Law Kawasan Asia Tenggara - Heribertus Jaka Triyana, Heribertus Jaka Triyana (Fakultas Hukum Universitas Katolik Widya Mandira Kupang, 2012)
This article, the role and function of the ASEAN Intergovernmental Commission on Human Rights aims to critically examine its mandates to disseminate and to promote human rights in South East Asian countries where Indonesia is taken for example. It is devided into five consecutive in depth discussions in terms of its legal base of its authoritative powers derived from the ASEAN Charter and from the ASEAN Human Rights Declation; possible crash between normativity and facts; widening legal gaps between national and regional human rights norms and mechanisms; possibility of legal vacuum for implementing and monitoring mechanism at the national and regional levels; and imminent conflicts of norms on human rights norms and mechanisms. Finally, it reveals that the role and function of the ASEAN Intergovernmental, Commission on contribute to dynamic discussion ending with imminent challanges problems and opportunity for further elaboration at strategic, operatiuonal and tactical level of implementation. Indonesia, as one of the forerunner of the ASEAN shall gain this momentum to voice up the Indonesian national legal system for human rights protection as a role model in ASEAN level. Key words : ASEAN, to promote, rule of law